Body Mass Index, Genetic Susceptibility, and Risk of Complications Among Individuals with Crohn's Disease - Pringle, Patricia L (Inflamm Bowel Dis, 2015)
BACKGROUND: Obesity is associated with systemic and intestine-specific inflammation as well as alterations in gut microbiota, which in turn impact mucosal immunity. Nonetheless, a specific role of obesity and its interaction with genetics in the progression of Crohn's disease (CD) is unclear. METHODS: We conduced a cross-sectional study of CD patients enrolled in Prospective Registry in Inflammatory Bowel Disease Study at Massachusetts General Hospital (PRISM). Information on diagnosis of CD and its complications were collected and confirmed through review of medical records. A genetic risk score was calculated using previously reported single nucleotide polymorphisms (SNPs) associated genome-wide with CD susceptibility. We used logistic regression to estimate the effect of body mass index (BMI) and its interaction with genetic risk on risk of CD complications. RESULTS: Among 846 CD patients, 350 required surgery, 242 with penetrating disease, 182 with stricturing disease, and 226 with perianal disease. There were no associations between obesity (BMI ≥ 30) and risk of perianal disease, stricturing disease, or surgery. Compared to normal weight individuals with BMI < 25, obesity was associated with lower risk of penetrating disease (OR = 0.56, 95% CI 0.31-0.99). This association persists among a subgroup of participants with available BMI prior to development of penetrating disease (OR = 0.40, 95% CI 0.16-0.88). There were no interactions between BMI and genetic risk score on risk of CD complications (All P(interaction) > 0.28). CONCLUSION: Our data suggest that obesity does not negatively impact long-term progression of CD, even after accounting for genetic predisposition.